Hubungan Usia Kehamilan dan Jenis Persalinan dengan Lama Rawat Inap Kasus Low Birth Weight di RS PKU Muhammadiyah Surakarta Tahun 2022 - Pratama, Bangkit Ary (Unit Penelitian dan Pengabdian Masyarakat Politeknik Kesehatan Bhakti Mulial, 2024)
Length of stay can be influenced by many factors such as clinical factors and non-clinical factors. Length of stay assessment can be used to determine the effectiveness and efficiency of services provided by the hospital. The aim of this study was to determine the relationship between gestational age and type of delivery with the length of stay in cases of low birth weight at PKU Muhammadiyah Surakarta Hospital. This quantitative research uses a correlative descriptive design with a retrospective approach. The research sample was all cases of low birth weight in 2022 at the PKU Muhammadiyah Surakarta Hospital, totaling 117 patients and taken as a total sampling. The research data comes from indexing reports and medical record documents of inpatients with low birth weight cases in 2022 at the PKU Muhammadiyah Surakarta Hospital. Data analysis was carried out univariately to see the frequency distribution of each variable and bivariate analysis using the Chi Square formula to analyze the relationship between variables. The results of the analysis of the relationship between gestational age and length of stay in low birth weight cases showed that the calculated Chi Square value was (7.874) > Chi Square table (3.481) and the p-value (0.005) < 0.05. The results of the analysis of the relationship between type of delivery and length of stay in low birth weight cases showed that the calculated Chi Square value was (2.887) < Chi Square table (3.481) and p-value (0.089) > 0.05. The conclusion of this study is that gestational age is related to the length of stay in low birth weight cases at PKU Muhammadiyah Surakarta Hospital, while the type of delivery is not related to the length of stay in low birth weight cases at PKU Muhammadiyah Surakarta Hospital.